The Construction of the Authority of The Ethics Committee in Regional House of Representatives regarding Ethics Enforcement : A Case Study of the Makassar City DPRD - Hisbullah, Hisbullah; Sofyan; Andi Rezal Jauhari; Annisa Zalsabillah; A Tenripadang (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2024)
The core issue of this research is how the Honorary Body at the Regional People's Representative Council (DPRD) of Makassar City constructs the enforcement of the code of ethics. This study is a field research employing an empirical juridical approach and normative theological approach (syar'i). The data were obtained from primary sources such as legislation and other secondary sources. Data collection methods included interviews and documentation. Data analysis was conducted through stages of data presentation, reduction, editing, data analysis, and drawing conclusions. The results of this study indicate that: 1) The Honorary Body of the DPRD of Makassar City was established based on legislation and functions as an enforcer of the code of ethics; 2) The Honorary Body of the DPRD of Makassar City performs its duties based on the autonomous regional agreement under DPRD Regulation No. 1 of 2018 concerning Rules of Procedure; 3) The issue of code of ethics enforcement in the DPRD of Makassar City is the formal enforcement factor, which can only be reported by the leadership, resulting in an ineffective check and balance. It is recommended that the DPRD of Makassar City grants freedom to the public and involves community elements in monitoring the code of ethics for members of the DPRD of Makassar City.